Implementation of Itinerant Classrooms as an Educational Strategy for Pedagogical Knowledge Recovery in Basic Education Students - Núñez-Hernández, Corina; Mantilla, Cristina; Buele, Jorge (Journal of Ecohumanism, 2024)
The global COVID-19 pandemic resulted in academic setbacks due to the loss of learning, the effects of which began to become evident during the progressive return to in-person classes, highlighting the need to work on re-education processes. This study examines the effectiveness of itinerant classrooms in facilitating learning recovery among Basic Education students following the impact of the COVID-19 pandemic. A pedagogical support intervention was implemented for 304 students across educational institutions nationwide. A quasi-experimental design with a quantitative approach was employed, utilizing pre-test and post-test assessments to evaluate mathematics performance. The results demonstrated a significant improvement in student grades after the intervention, with the complete elimination of scores in the lower range. These findings underscore the effectiveness of itinerant classrooms as a mobile educational strategy that addresses the needs of students in marginalized communities. The research highlights the importance of an inclusive approach to pedagogical recovery, promoting collaboration among educators, psychologists, and families to comprehensively address academic underachievement.